Impact of irrigation with Lake Abaya water on soil quality – southern Rift Valley, Ethiopia. Issue 7 (27th June 2022) - Setegn, Yalelet Abera; Kassa, Kinfe; Dagalo, Samuel; Tsegaye, Dereje
Abstract: The study's aim was to assess the impact of using water from Lake Abaya for irrigation and its impact on soil quality at Mirab Abaya, Ethiopia. Six water samples from the edge of Lake Abaya and 30 (18 irrigated and 12 rain-fed) composite soil samples from farm lands in Wajifo, Fura and Algae were collected. Analyses showed that the use of water from Lake Abaya will bring a soil salinity hazard in future. The soil analyses showed variations in space and time in the physico-chemical components in the study area. The highest salinity was reported from Algae, the closest site to the Lake. The highest soil alkalinity was reported from Wajifo, which has a long irrigation history. The irrigated soils reported higher salinity than the rain-fed soils, indicating that water from Lake Abaya can affect irrigated soil quality. In general, Lake Abaya water is not suitable for salt-sensitive crops and caution is required in using it for irrigation. HIGHLIGHTS: Irrigation water quality is equally important as drinking water quality for sustainable and efficient irrigation project implementation. If the irrigation water quality deteriorates it has its own impact on soil quality. Due to that, irrigation water quality assessments will be mandatory for the implementation of efficient irrigation projects.